Investigations on Kaempferol, Quercetin and Other Flavonoids in Aquatic Plants of Iraqi Marshlands-I - Al-Sa’idy, Hussein Ali Hussein; Kamil Hamid, Hussein (Asian Journal of Pharmaceutical Research and Development, 2023)
Aquatic plants are versatile source of phytochemicals that are of significant biological influences particularly, the flavonoids and their glycosidic derivatives distributed in different plant parts including fruits, seeds, leaves, flowers, stem, roots and rhizomes. Most of the reported biological influences are reported to be expressed by quercetin, kaempferol, isorhmnatin, and their glycosidic derivatives, particularly, rutin. In this survey, we summarized the reported flavonoids types, content and factors affecting their extracts contents of three aquatic plants Nuphar, Najas and Nymphoides detected in the Iraqi central marshlands, in provenance of Thi-Qar. Surveying the phytochemical investigations regarding Nuphar species of reported abundance of polyphenolic compounds content including identified and quantified phenolic acids, flavonoids like flavonols and flavonones, particularly, in their leaves. However, flavonoids/their derivatives types and quantities in various parts extracts are not reported to the extent of our knowledge although they are presumed to contribute to the reported biological influence of the plant on one hand. On the other hands, regarding Najas species, few reports have identified the existence of flavonoids as well as other phenolic compounds, although, total quantification to the phenolic compounds, flavonoids and tannins are reported rather than identifying the individual flavonoid in the plant extracts. Only single report demonstrates the total phenolic, flavonoids and tannin contents of ethyl acetate extract of Najar minor according to our survey. Regarding Nymphoides species, the extraction level flavonoids as lipophilic compounds as well as their much polar glycosidic derivatives is depending on the solvent polarities. In general, in most of Nymphoides species the ethanolic extract querectin, methylquercetin and kaempferol flvonoides/their derivatives are identified individual flavonoids/quantified to be more than one fold of that in the aqueous extracts. Finally, the manner/position of glycosylation as well as glycosides sugar resides acylation vary among the Nymphoides species. In general, single 3-O- or di 3,4’-O- glycosylation pattern is noticed in kaempferol, quercetin and isorhamnetin. The multiply diverse glycosylation, methylation as well as acylation pattern of Nymphoides species flavonoids may explains their identification in various plant part/extracts besides the variation in their biological activities potentials.